The foundation of english learning to equip vocational students in higher education to face industrial era 4.0 - Pambudi, Haryo Aji; Kaliaskarova, Ainur (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
Industry 4.0, originally centered on manufacturing, has significantly evolved, influencing production and how individuals learn and develop skills. As vocational education is pivotal for skill development, it must swiftly adapt to the changing landscape of Industry 4.0, wherein English proficiency holds a crucial position. To enhance English learning effectively in preparation for the Industry 4.0 era, it is essential to understand the beliefs of vocational students, especially in higher education. This research utilized a survey method, employing a novel questionnaire to gauge these beliefs that can be useful information to shape the foundation of English learning. The study involved 258 students of the vocational program in higher education. The research findings demonstrated that the participants held positive beliefs concerning English learning. These favorable beliefs encompassed various aspects, including language learning methods, language skills with a focus on strategy awareness, the perception of English as integral to their careers, the utilization of authentic materials and technology as learning resources, the willingness to be self-directed learners, and the recognition of the life values acquired through English learning. Furthermore, the students held a functional view of language, underlining its practicality.